Early Effects of Prolonged Cardiac Arrest and Ischemic Postconditioning during Cardiopulmonary Resuscitation on Cardiac and Brain Mitochondrial Function in Pigs. (July 2017) - Matsuura, Timothy R.; Bartos, Jason A.; Tsangaris, Adamantios; Shekar, Kadambari Chandra; Olson, Matthew D.; Riess, Matthias L.; Bienengraeber, Martin; Aufderheide, Tom P.; Neumar, Robert W.; Rees, Jennifer N.; McKnite, Scott H.; Dikalova, Anna E.; et al.
Abstract: Background: Out-of-hospital cardiac arrest (CA) is a prevalent medical crisis resulting in severe injury to the heart and brain and an overall survival of less than 10%. Mitochondrial dysfunction is predicted to be a key determinant of poor outcomes following prolonged CA. However, the onset and severity of mitochondrial dysfunction during CA and cardiopulmonary resuscitation (CPR) is not fully understood. Ischemic postconditioning (IPC), controlled pauses during the initiation of CPR, has been shown to improve cardiac function and neurologically favorable outcomes after 15 min of CA. We tested the hypothesis that mitochondrial dysfunction develops during prolonged CA and can be rescued with IPC during CPR (IPC-CPR). Methods: A total of 63 swine were randomized to no ischemia (Naïve), 19 min of ventricular fibrillation (VF) CA without CPR (Untreated VF), or 15 min of CA with 4 min of reperfusion with either standard CPR (S-CPR) or IPC-CPR. Mitochondria were isolated from the heart and brain to quantify respiration, rate of ATP synthesis, and calcium retention capacity (CRC). Reactive oxygen species (ROS) production was quantified from fresh frozen heart and brain tissue. Results: Compared to Naïve, Untreated VF induced cardiac and brain ROS overproduction concurrent with decreased mitochondrial respiratory coupling and CRC, as well as decreased cardiac ATP synthesis. Compared to Untreated VF, S-CPR attenuated brain ROS overproduction but had no other effect on mitochondrial function in the heart or brain. Compared to Untreated VF, IPC-CPR improved cardiac mitochondrial respiratory coupling and rate of ATP synthesis, and decreased ROS overproduction in the heart and brain. Conclusions: Fifteen minutes of VF CA results in diminished mitochondrial respiration, ATP synthesis, CRC, and increased ROS production in the heart and brain. IPC-CPR attenuates cardiac mitochondrial dysfunction caused by prolonged VF CA after only 4 min of reperfusion, suggesting that IPC-CPR is an effective intervention to reduce cardiac injury. However, reperfusion with both CPR methods had limited effect on mitochondrial function in the brain, emphasizing an important physiological divergence in post-arrest recovery between those two vital organs.